Gay Politics Goes Mainstream: Democrats, Republicans and Same‐sex Relationships. (16th December 2021) - Fernández, Raquel; Parsa, Sahar
Abstract : Attitudes towards same‐sex relationships in the USA have changed radically over a relatively short period of time. After remaining fairly constant for over two decades, opinions became more favourable starting in 1992—a presidential election year in which the Democratic and Republican Parties took opposing stands over the status of gay people in society. What roles did political parties and their leaders play in this process of cultural change? Using a variety of techniques, including machine learning, we show that the partisan opinion gap emerged substantially prior to 1992—in the mid to late 1980s—and did not increase as a result of the political debates in 1992–3. Furthermore, we identify people with a college‐and‐above education as the potential 'leaders' of the process of partisan divergence.